PENERAPAN METODE PEMBELARAN ROLE REVERSAL QUESTION DALAM MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PKn ANTI KORUPSI KELAS V SDS KARTINI PANIPAHAN - Pancarani, Amalia; sujarwo, Sujarwo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objective of this research was to describe and identify the improvement in learning outcomes from the application of the role reversal question method in Anti-Corruption Civic Education for grade V students at SDS Kartini Panipahan. The design of this research was Classroom Action Research (CAR), with the object of the research being the application of the role reversal question learning method to enhance student activity and learning outcomes in Anti-Corruption Civic Education. The results and discussions of this research concluded that the PKn learning using the active learning method of role reversal question could improve the learning outcomes of grade V students at SDS Kartini Panipahan. The steps in the active learning model of role reversal question included: the teacher creating questions related to the material before the learning activity began, explaining the learning activities, dividing students into several groups, assigning students to conduct group discussions, assigning students to create individual questions, conducting Q&A sessions by swapping roles, and providing feedback on students' answers. This was indicated by the students who scored ≥70 in cycle I increasing by 25% from an initial condition of 39% to 69%. Subsequently, the students who scored ≥70 in cycle II experienced an increase of 28%, reaching 93%. The average score in cycle I increased by 8.75% from the initial condition of 57.73 to 78.52, and in cycle II, the average score increased again by 10.97%, reaching 86.25.